Emotion Regulation in Close Relationships: The Role of Individual Differences and Situational Context - Chen, Wan-Lan; Liao, Wan Ting (Frontiers in Psychology, 2021)
A substantial amount of research has examined the role of individual differences in the regulation of emotion and the impact of emotion regulation on mental health; however, few studies have covered the role of situational context in the selection of emotion regulation strategies. In this paper, we investigate the extent to which an individual’s choice of emotion regulation strategy is affected by factors such as emotional intelligence, the person with whom one is in conflict, situational sense of control, and the individual’s aim in dealing with the conflict. A total of 300 participants (46.67% female) between the ages of 21 and 35 were recruited from the community ( female’s mean age = 28.14, SD = 4.49; male’s mean age = 28.12, SD = 4.32). Participants filled out a set of questionnaires related to their emotion intelligence and emotion regulations they used in two interpersonal incidents with parents and partner. Structural equation modeling was used for data analyses. Results showed that positive correlation between emotional intelligence and cognitive reappraisal, in contrast to previous studies, a positive correlation between emotional intelligence and repression was found. Moreover, the person one is interacting with influences the degree to which one’s sense of control impacts the choice of emotion regulation strategy. For example, in the event of conflict with one’s parents, the degree of situational control has little impact on emotion regulation; however, in conflicts with spouses or partners, women have more situational control and are more likely to use cognitive reappraisal or suppression. Regarding the relationship between the goal of emotion regulation and the strategies used, this study found that they are moderated by gender and the persons involved; for example, when maintaining the relationship is the primary goal of emotion regulation, cognitive reappraisal is more likely the strategy of choice for men involved in a conflict with their partner and for women involved in a conflict with their parents. Overall, the results confirm that emotion regulation is affected by both individual and situational factors, indicating the importance of adopting a dynamic approach when investigating emotion regulation.